Case Study : A Great Recovery Of Malaysia Airlines - Abdul Hamid, Azni Syafawati (2005)
Previously a goverment agency, later known as Malaysian Airline System (MAS) embarked on a system of corporate governance that would ensure the fulfillment of its role not only as a national carrier but also as a corporate citizen centered on being responsible to its shareholders.